2021
DOI: 10.1021/acs.est.1c02818
|View full text |Cite
|
Sign up to set email alerts
|

Leaching and In Vivo Bioavailability of Antimony in PET Bottled Beverages

Abstract: Antimony (Sb) may leach from polyethylene terephthalate (PET) materials into bottled water under improper storage conditions, particularly at high temperatures, leading to potential Sb chronic exposure and adverse health effects. However, Sb leaching may be promoted by various beverage constituents, which has received limited attention to date. In addition, few studies have considered Sb bioavailability in beverages and the influence of the beverage matrix on Sb bioavailability. In this study, PET-bottled beve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…To reduce the risks associated with dietary exposure to Sb, it is necessary to conduct studies aimed at determining the transfer and bioavailability of Sb in different food matrices (Xu et al, 2021).…”
Section: Risk Management Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce the risks associated with dietary exposure to Sb, it is necessary to conduct studies aimed at determining the transfer and bioavailability of Sb in different food matrices (Xu et al, 2021).…”
Section: Risk Management Strategiesmentioning
confidence: 99%
“…For its part, Xu et al (2021) studied the leaching and in vivo bioavailability of Sb in PET bottled beverages, especially when they are stored in poor conditions, finding that carbonated and protein-rich beverages exhibited a higher risk of exposure due to high leaching of Sb and the high bioavailability compared to other categories of beverages. The beverages considered were soft drinks, fruit juices, tea, sports drinks, protein drinks and coffee drinks.…”
Section: Exposure and Risk Assessmentmentioning
confidence: 99%
“…The presence of Sb in PET-bottled drinks could be attributed to its usage as a catalyst during the production of PET, mostly in the Sb trioxide form [48,49]. Xu et al [50] examined the leaching and bioavailability of Sb in PET-bottled beverages across six categories (carbonated, fruit juices, tea, sports, protein, and coffee beverages). They found that high temperature and low pH exposure could lead to excessive Sb leaching, 1.1-10.9 times higher than before exposure.…”
Section: Elementsmentioning
confidence: 99%
“…However, an increasing number of recent analyses have indicated that Sb may be released into drinking water from polyethylene terephthalate (PET) bottles [47,48]. Antimony trioxide (Sb2O3) is used in PET polymers production as a catalyst and it may leach into bottled beverages under inappropriate storage conditions, such as exposition to high temperature or sunlight [47].…”
Section: Antimonymentioning
confidence: 99%